2020
DOI: 10.1371/journal.pone.0234158
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of woody plant species diversity during a dry season in a savanna environment using the spectral and textural information derived from WorldView-2 imagery

Abstract: Remote sensing techniques are useful in the monitoring of woody plant species diversity in different environments including in savanna vegetation types. However, the performance of satellite imagery in assessing woody plant species diversity in dry seasons has been understudied. This study aimed to assess the performance of multiple Gray Level Co-occurrence Matrices (GLCM) derived from individual bands of WorldView-2 satellite imagery to quantify woody plant species diversity in a savanna environment during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Numerous research in the field of forestry and ecology have exhausted this approach more specifically in enumerating species diversity. Though this approach is the most favoured information extraction method, it can under-or-overestimate the number of species that potentially exist on the ground [ 48 ]. In contrast, continuous-scale assessment/modelling converts unique species data into a continuous diversity scale, thus allowing stretching the ability to estimate as many species as possible.…”
Section: Species Discrimination Using Categorical-scale and Continuou...mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous research in the field of forestry and ecology have exhausted this approach more specifically in enumerating species diversity. Though this approach is the most favoured information extraction method, it can under-or-overestimate the number of species that potentially exist on the ground [ 48 ]. In contrast, continuous-scale assessment/modelling converts unique species data into a continuous diversity scale, thus allowing stretching the ability to estimate as many species as possible.…”
Section: Species Discrimination Using Categorical-scale and Continuou...mentioning
confidence: 99%
“…They, then, used linear regression to assess the relationship between the diversity index and eight Grey Level Co-occurrence Matrices (GLCM) extracted from Landsat-7 achieving R 2 = 0.01–0.60. [ 48 ] estimated woody plant species diversity in Montane savanna area (651 ha), dominated by morphologically similar woody plant species. The study applied the all-subsets regression to correlate Shannon diversity index quantified from field inventory of 15 m radius plots with GLCM derived from individual bands of WorldView-2 imagery.…”
Section: Remote Sensing Of Savanna Woody Plant Species Diversity Usin...mentioning
confidence: 99%
“…The relevance and application of remote sensing for natural forest studies have been widely demonstrated by various authors. These applications include questions linked to forest biophysical parameter inventory, forest biochemical mapping [20], tree species discrimination and mapping [21,22], carbon stocks estimation [23][24][25], forest land cover change mapping [26][27][28][29], biodiversity assessment and monitoring [30][31][32], assessment of forest extent [33], and tree crown delineation [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%